The Influence of Self-Directed Dialog Toward Students' Speaking Ability in SMAN 20 BATAM - Lala Imaliyah; Desty Febria; Marsevani, Maya (English Language Education, Universitas Internasional Batam, 2024)
This study aimed to determine the influence of self-directed discourse on students' speaking abilities in SMAN 20 BATAM. The self-directed dialogue technique is a practice that integrates practical ways to communicate or contextual practice with simulations. Self-directed dialogue encourages students to use their words to create discourse; group learning can do this, but the guiding idea is that learning is the responsibility of the individual students. Students feel more comfortable explaining why they want to develop by using their own language because it is more relatable to them. One method that can help students become better speakers is self-directed dialogue. Speaking skills are divided into four categories: fluency, vocabulary, grammar, and pronunciation. A one-group pre- and post-test design was employed in the pre-experimental method by the researchers, this four-week study involved four meetings, including treatment. 46 students in Phase-F (the eleventh class) of Brilliant were the samples that were collected. Speaking rubrics were used to collect the data, which SPSS v26 was then used to process. According to the study's findings, students’ development scores on average were 38.89 on the pre-test and 65.39 on the post-test. The statistical data indicates that the null hypothesis is rejected and the alternative hypothesis is accepted, as indicated by the significance value of the t-test (0,000 < 0,05). Based on the results, the researcher draws the conclusion that Phase-F students at SMAN 20 BATAM can enhance their speaking abilities by introducing self-directed discourse. This suggests that students' speaking abilities can be enhanced through self-directed dialogue in an effective and significant way.